Identification of a nonlinear polynomial compartmental system of (α + β) order by a linearization method - Hebri, B.; Cherruault, Y. (Mathematical Modelling and Analysis, 2006)
A linearization method is used for identifying a nonlinear polynomial compartmental system of (α + β) order. We bring back the nonlinear model to a linear one for which a method, developed for Michaelis‐Menten systems in a previous paper, can be used. First Published Online: 14 Oct 2010